The 3-D kinematic analysis of different tennis serve - Lin, H.; Chang, J.; Chien, J.; Tseng, C. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The key to success for a good tennis player is to be able to take the advantages of serving and keep the serve. The world's professional tennis players in front of the world rankings, most have very excellent serve skills. Two different footwork techniques in tennis serve used by most professional tennis players are the foot-up and foot-back serve technique. Most researchers investigated the differences between these footwork techniques using 2-D kinematics data (Elliott et al, 1983). However, little evidence has demonstrated that which serve technique is better (Bylak et al, 1998) or if a difference exists between foot-up and foot-back technique using 3-D analysis (Elliott et al, 1996). The purposes of this study were to investgate the differences in 3-D kinematics between the foot-up and foot-back tennis serve techniques.